Serologic survey of humans for flavivirus West Nile in Southern Moravia (Czech Republic) - Hubálek, Zdenek; Kríz, Bohumír; Halouzka, Jirí (Central European journal of public health, 2011)
A serosurvey for West Nile virus (WNV) was carried out in 525 persons, using a plaque-reduction neutralization microtest (PRNmicroT) with Vero cells and Egyptian topotype Eg-101 strain as test virus. The blood sera were collected in four South-Moravian districts (Hodonin 44 persons, Breclav 102 persons, Znojmo 170 persons, Jihlava 209 persons) of the Czech Republic in the years 1988 and 1989, and stored at -20 degrees C. Antibodies to WNV were detected in only three humans (0.6% seropositivity): one person each in the districts of Hodonin (2.3% persons positive), Breclav (1.0% positive) and Jihlava (0.5% positive), with the titres of 1:64, 1:32, and 1:32, respectively. All the three sera were negative for antibody to tick-borne encephalitis virus. The results indicate that activity of WNV in southern Moravia was very low before 1990.
Keywords: West Nile virus; Česká republika; Neutralization Tests; Middle Aged; mužské pohlaví; plakové testy; Antibodies, Viral; Adult; mladý dospělý; Czech Republic; Young Adult; ženské pohlaví; západonilská horečka; Humans; Viral Plaque Assay; protilátky virové; lidé středního věku; neutralizační testy; dospělí; Flavivirus; Female; virus západního Nilu; West Nile Fever; lidé; Male